“Neither Have I Gone Mad nor Stupid”: Writing as a Defense of Dignity in Agustina González López (1891-1936) - Moreno Lago, Eva María (Universidad Pedagógica y Tecnológica de Colombia, 2023)
Agustina González López, “la zapatera” (the shoemaker), is an almost unknown writer, painter and politician from Granada whose literary work has not been analyzed nor appreciated. This article will delve into the rhetoric strategies employed by the author in her work Justificación (1928) to safeguard her dignity. The objective is to discuss, in terms of gynocriticism and literary studies, the writing of this enigmatic woman. The results of the analysis reveal, on one hand, method to disempower women was to accusing them of being abnormal for disobeying social standards, and on the other hand, the writer’s ability to dismantle these discourses. Thus, the aim is to demonstrate that writing was a way to understand how women were perceived by society and, simultaneously, to seek their own identity outside of established roles and patterns.